Clinical profile of diabetic sensorimotor polyneuropathy in a tertiary hospital in Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Objective:To determine the frequency, severity, and determinants of diabetic sensorimotor polyneuropathy (DSPN) in adults from a tertiary hospital in Northwestern Nigeria.Materials and Methods:A cross-sectional hospital-based study where 400 type 2 diabetes mellitus patients attending clinic in a tertiary hospital were screened for DSPN and graded for severity using the United Kingdom screening test (UKST). Logistic regression was used to identify independent predictors of DSPN after controlling for other covariates. All data were analysed using Predictive Analysis Software (PASW) version 18.0 for Windows (SPSS Inc., Chicago, IL, USA).Results:Frequency of DSPN among the study (comprising 59 males and 66 females) subjects was 125 (31.2%), of which 105 (26.3%) patients were symptomatic. Sixty-eight (17%) patients were at high risk of developing diabetic feet ulceration. Multivariate logistic regression showed that marital status (OR = 0.55; 95% CI = 0.31-0.98) was protective, while the duration of diabetes (OR 5.80; 95% CI = 3.38-9.95) was a significant independent predictor of DSPN.Conclusions:The high frequency of DSPN in patients with high risk of feet ulceration from this study prompt the need to adopt efficacious and less-expensive strategies for screening and preventing diabetic foot complications in our resource-constraint settings.